Demand Variability, Supply Shocks and the Output-Inflation Tradeoff - Froyen, Richard T.; Waud, Roger N. (The Review of Economics and Statistics, 1985)
This paper examines the shift in the relation between the inflation rate and the rate of growth of real output which has occurred in the United States over the past three decades, and attempts to assess the relative importance of three possible lines of explanation: a) the new classical view of the output-inflation tradeoff, initially specified by Lucas; b) the effect of supply-side shocks, such as energy prices; c) the effect of inflation variability on the natural rate of real output, as hypothesized by Milton Friedman. The paper concludes that b) and c) seem to have played a significant role in the observed shift from a positive to a negative correlation between the rate of inflation and the rate of real output growth, but that a) did not.